The lost English girl - Kelly, Julia, 1986- (Gallery Books, 2023)
"Liverpool, 1935: Raised in a strict Catholic family, Viv Byrne knows what's expected of her: marry a Catholic man from her working-class neighborhood and have his children. However, when she finds herself pregnant after a fling with Joshua Levinson, a Jewish man with dreams of becoming a famous Jazz musician, Viv knows that a swift wedding is the only answer. Her only solace is that marrying Joshua will mean escaping her strict mother's scrutiny. But when Joshua makes a life-changing choice on their wedding day, Viv is forced once again into the arms of her disapproving family. Five years later and on the eve of World War II, Viv is faced with the impossible choice to evacuate her young daughter, Maggie, to the countryside estate of the affluent Thompson family. In New York City, Joshua gives up his failing musical career to serve in the Royal Air Force, fight for his country, and try to piece together his feelings about the family, wife, and daughter he left behind at eighteen. However, tragedy strikes when Viv learns that the countryside safe haven she sent her daughter to wasn't immune from the horrors of war. It is only years later, with Joshua's help, that Viv learns the secrets of their shared past and what it will take to put a family back together again. Telling the harrowing story of England's many evacuated children, bestselling author Julia Kelly's The Lost English Girl explores how one simple choice can change the course of a life, and what we are willing to forgive to find a way back to the ones we love and thought lost"--